Lord Salvesen: the philanthropist's path to making sense of early twentieth-century Scotland - Khoo, Annabelle Yi Xian (Nanyang Technological University, 2022)
This thesis investigates the life and career of Edinburgh-born lawyer, judge and Liberal political activist, Lord Edward Theodore Salvesen (1857–1942). Examining Lord Salvesen’s experiences facilitates the wider analysis of the multifaceted social, cultural, and imaginative transformation of Scottish society during and in the aftermath of World War I (WWI). Studying Lord Salvesen’s experiences enables us to understand how the contours of Victorian voluntary activity and philanthropy that had conditioned Scottish society’s original response to WWI began to shift by the end of the war. It facilitates the tracking of how confident appeals for wartime military registration started to turn to greater concern over the needs of ordinary soldiers. Such a shift mirrored wider socio-political shifts within Britain. Still, more importantly, Lord Salvesen’s involvement with the developing idea of ‘living memorials’ fashioned a technique by which the voluntary and philanthropic world responded to the challenge of modernity. While Lord Salvesen was, in essence, caught in the shifting socio-political Scottish landscape, he was not merely a passive figure. One cannot dismiss his attempts at exercising his own agency as he navigated and made sense of the war-impacted Scottish society. Despite his initial practice of philanthropy being a conditioned response to WWI, his intensified engagements with voluntarism after personal familial losses resulted in the public’s acknowledgement of his public mindedness. That his wartime fund raising efforts placed emphasis on the welfare of the Scottish military veterans, as well as the identities and worth of the Scottish Lowland regiments propelled Lord Salvesen to be recognised as being a voice for the underdogs of the Scottish society. This, in turn, enhanced cross-class social respect for him. The examination of Lord Salvesen, therefore, allows for the understanding of his personal lived experiences. More significantly, it is through him that one can note wider changes witnessed in Scottish society, particularly how Scottishness had developed in the early twentieth-century. Lord Salvesen was a product and agent of change—one who had interactions that transcended class, regions and nationalities. Being at the heart of interweaving multi-dimensional exchanges and processes, Lord Salvesen, thus, ultimately was a microcosm of the twentieth-century Scottish society.